Pharmacological treatment and vaccines in monkeypox virus: a narrative review and bibliometric analysis - Shamim, Muhammad Aaqib; Satapathy, Prakisini; Padhi, Bijaya Kumar; Veeramachaneni, Sai Dutt; Akhtar, Naushaba; Pradhan, Anindita; Agrawal, Abhimanyu; Dwivedi, Pradeep; Mohanty, Aroop; Pradhan, Keerti Bhusan; Kabir, Russell; Rabaan, Ali A.; et al. (Frontiers in Pharmacology, 2023)
Mpox (earlier known as monkeypox) virus infection is a recognized public health emergency. There has been little research on the treatment options. This article reviews the specific drugs used to treat mpox virus infection and the vaccines used here. Instead of focusing on the mechanistic basis, this review narrates the practical, real-life experiences of individual patients of mpox virus disease being administered these medicines. We conducted a bibliometric analysis on the treatment of the mpox virus using data from several databases like PubMed, Scopus, and Embase. The research on this topic has grown tremendously recently but it is highly concentrated in a few countries. Cidofovir is the most studied drug. This is because it is indicated and also used off-label for several conditions. The drugs used for mpox virus infection include tecovirimat, cidofovir, brincidofovir, vaccinia immune globulin, and trifluridine. Tecovirimat is used most frequently. It is a promising option in progressive mpox disease in terms of both efficacy and safety. Brincidofovir has been associated with treatment discontinuation due to elevated hepatic enzymes. Cidofovir is also not the preferred drug, often used because of the unavailability of tecovirimat. Trifluridine is used topically as an add-on agent along with tecovirimat for ocular manifestations of mpox virus disease. No study reports individual patient data for vaccinia immune globulin. Though no vaccine is currently approved for mpox virus infection, ACAM 2000 and JYNNEOS are the vaccines being mainly considered. ACAM 2000 is capable of replicating and may cause severe adverse reactions. It is used when JYNNEOS is contraindicated. Several drugs and vaccines are under development and have been discussed alongside pragmatic aspects of mpox virus treatment and prevention. Further studies can provide more insight into the safety and efficacy of Tecovirimat in actively progressing mpox virus disease.